2023
DOI: 10.3390/d15050647
|View full text |Cite
|
Sign up to set email alerts
|

Bryophytes in a Changing World: Understanding Distribution Patterns, Risks, and Conservation

Abstract: Bryophytes are a group of small, non-vascular plants that include mosses, liverworts, and hornworts [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…In addition, they also play an important role in sustaining the lives of number of micro, meso and macro fauna by providing safe nesting site, optimal temperature conditions and act as rich nutrient source [6,15]. Studies on moss micro fauna is not very common, and whatever studies that are available are on moss associated fauna in natural habitats, such as forest floor, streams, mountains etc [1,13,16]. However, almost no significant studies are reported on fauna associated with moss dwelling on man-made structures…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, they also play an important role in sustaining the lives of number of micro, meso and macro fauna by providing safe nesting site, optimal temperature conditions and act as rich nutrient source [6,15]. Studies on moss micro fauna is not very common, and whatever studies that are available are on moss associated fauna in natural habitats, such as forest floor, streams, mountains etc [1,13,16]. However, almost no significant studies are reported on fauna associated with moss dwelling on man-made structures…”
Section: Discussionmentioning
confidence: 99%
“…Bryophytes are tiny, autotrophic, non -vascular cryptogams, which are ubiquitous in distribution [1]. They are referred to as "Amphibians of the Plant Kingdom" due to their dual lives on both water and land.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Species distribution models are widely utilized in conservation biogeography due to their ability to estimate potential range shifts for species and communities in response to climate change. Moreover, they have been successfully used to study the distribution of bryophytes in a variety of ecosystems, including identifying areas of high conservation value [ 93 , 94 ]. Consequently, they represent a valuable tool for informing and guiding conservation management planning.…”
Section: Discussionmentioning
confidence: 99%